(untitled) (CIPEEX, 2022)
ANTERIOR CRUCIATE LIGAMENT INJURY (ACLI) IS VERY COMMON IN SPORTS, AND OFTEN REQUIRES SURGICAL TREATMENT TO RESOLVE THE PROBLEM, BUT MANY PATIENTS MAY EXPERIENCE SOME COMPLICATIONS SUCH AS PAIN, INSTABILITY OR STIFFNESS AFTER SURGICAL RECONSTRUCTION. THEREFORE, THE WORK IS A CASE REPORT ON A RARE CASE OF INJURY IN CYCLOPS AFTER SURGICAL REPAIR OF THE ANTERIOR CRUCIATE LIGAMENT (ACL). THE OBJECTIVE WAS TO REPORT A CASE OF POST-SURGICAL ORTHOPEDIC COMPLICATION OF RECONSTRUCTION OF THE ANTERIOR CRUCIATE LIGAMENT (ACL) OF THE KNEE IN A 19-YEAR-OLD ATHLETE UNDERGOING TREATMENT IN ANÁPOLIS. INFORMATION ON CLINICAL CONDITIONS AND MULTIDISCIPLINARY RECORDS WERE EXTRACTED FROM THE PATIENT’S MEDICAL RECORD AND COMPARED WITH BIBLIOGRAPHIES ON THE SUBJECT. IT IS KNOWN THAT THE CYCLOPS INJURY IDENTIFIED IN THE PATIENT IS ONE OF THOSE RARE COMPLICATIONS THAT OCCUR AFTER THE RECONSTRUCTION OF THE ANTERIOR CRUCIATE LIGAMENT (ACL) OF THE KNEE, AND IT IS A HYPERHEALING OF THE ACL GRAFT, FORMING SOMETHING SIMILAR TO A KELOID INSIDE OF THE JOINT, CAUSING PAIN AND BLOCKING THE ABILITY TO EXTEND THE KNEE. THERE WAS A NEW SURGICAL TREATMENT AT THE SITE, CALLED ARTHROSCOPY, WITH THE AIM OF DEBRIDING THE LESION. THEREFORE, AN IMPROVEMENT IN THE ATHLETE’S CLINICAL PICTURE WAS EVIDENCED, BEING ESSENTIAL TO DISCUSS IMPORTANT POINTS THAT CONFIGURED THIS EVOLUTION. IN VIEW OF THE RESULTS, FURTHER STUDIES ARE NEEDED ON THE INJURY IN CYCLOPS IN RELATION, MAINLY, TO PREDISPOSING FACTORS, EARLY DIAGNOSIS, BETTER TREATMENTS AND PREVENTION, SINCE ONLY IN 1990 WAS THE PORTRAYED INJURY PRIMARILY DESCRIBED IN THE LITERATURE.